Efficient and CO2-tolerant oxygen transport membranes prepared from high-valence B-site substituted cobalt-free SrFeO3−δ - Zhang, Z.; Chen, D.; Dong, F.; Shao, Zongping (Elsevier, 2015)
The simultaneous high oxygen permeability and high chemical stability of perovskites for use as oxygen transport membranes are of critical importance for applications in oxyfuel processes and as membrane reactors for coupling reactions. Here cobalt-free and CO2-tolerant SrFe0.8M0.2O3−δ (M=Zr, Mo, and W) were exploited as materials for oxygen transport membranes, which exhibited stable cubic phase structures in both air and CO2-containing atmospheres. At 850 °C and under the air/helium gradient across the membranes, oxygen permeation fluxes of 0.387, 0.216 and 0.201 mL cm−2 min−1 [STP] were reached for SrFe0.8Zr0.2O3−δ, SrFe0.8Mo0.2O3−δ and SrFe0.8W0.2O3−δ (membrane thickness: 1 mm), respectively. More importantly, relatively stable oxygen permeation fluxes of 0.262, 0.145 and 0.164 mL cm−2 min−1 were still reached for above three membranes correspondingly and maintained for almost 600 min when the sweep gas was switched to 10% CO2-containing helium when compared to the un-doped SrFeO3−δ membrane. Our findings suggest that the stable phase structure and improved CO2 resistance can be effectively achieved by facile doping of high-valence and redox-inactive transition metal ions into the SrFeO3−δ parent oxide. This process provides an efficient way for the development of CO2-tolerant oxygen transport membranes without applying other complex membrane structures (e.g., dual-phase membranes) or noble metals.